Efektifitas Kolom Dengan Tulangan Cold-Formed Type Hollow Dalam Memikul Beban Aksial - K.Budi Hastono (Universitas Muhammadiyah Surabaya, 2017)
AbstractAs part of the support component in the building structure, the column is a component that bears an external load and it will give rise to axial force, bending moment and shear force along its height. Pure concrete columns can support very small loads, but their load carrying capacity will increase considerably if added longitudinal bars. Larger strength enhancements can be made by providing lateral restraints in this longitudinal reinforcement. As a result of the compressive load, the column tends not only to shorten in the longitudinal direction but also expands in the lateral direction due to the poison's effect. This research will be carried out by testing the maximum axial load until the crack occurs in the reinforced concrete column with the planning of the two looks, the 20 x 20 x 60 cm column size with the dependent variable of longitudinal steel screw and Cold Formed (mild steel) type hollow steel. The results of this study The use of the column by using screw steel reinforcement is still more effective than by using cold-formed steel reinforcement. Columns with reinforced steel reinforcement have a lower strength of 44.4% of the column by using screw steel reinforcement. Keywords: Column, axial, cold-formed AbstrakSebagai bagian dari komponen penyokong dalam struktur bangunan, kolom merupakan komponen yang memikul beban luar dan itu akan menimbulkan gaya aksial, momen lentur dan gaya geser disepanjang ketinggiannya. Kolom beton murni dapat mendukung beban sangat kecil, tetapi kapasitas daya dukung bebannya akan meningkat cukup besar jika ditambahkan tulangan longitudinal. Peningkatan kekuatan yang lebih besar dapat dibuat dengan memberikan kekangan lateral pada tulangan longitudinal ini. Akibat beban tekan, kolom cenderung tidak hanya memendek dalam arah memanjang tetapi juga mengembang dalam arah lateral karena pengaruh poison. Penelitian ini akan dilakukan pengujian beban aksial maximum sampai terjadi retak pada kolom beton bertulang dengan perencanaan tampang dua, ukuran kolom 20 x 20 x 60 cm dengan variabel dependen tulangan longitudinal baja ulir dan tulangan Cold Formed ( baja ringan ) type hollow. Hasil dalam penelitian ini Penggunaan kolom dengan menggunakan tulangan baja ulir masih lebih efektif dari pada dengan menggunakan tulangan baja cold-formed. Kolom dengan tulangan baja col-formed mempunyai kekuatan lebih rendah 44, 4 % dari kolom dengan menggunakan tulangan baja ulir. Kata Kunci: Kolom, axial, cold-formed